1992
DOI: 10.1002/jat.2550120304
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry, morphometry and histopathology as biomarkers of benzo[a]pyrene exposure in brown bullheads (ameiurus nebulosus)

Abstract: Brown bullheads were given a single intraperitoneal dose of 0, 5, 25 or 125 mg kg-1 benzo[a]pyrene (BaP), a carcinogenic polycyclic aromatic hydrocarbon, and evaluated over 18 months. Flow cytometric analyses of hepatocyte DNA content indicated an increase in DNA synthesis in BaP-exposed fish prior to day 14 post-exposure. Thereafter, all flow cytometric variables returned to initial levels. Histopathological evaluation of livers from fish sampled at 18 months revealed significant differences among treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…This is in accordance with previous studies, which reported that presence of toxicants in the environment was not always associated with fluctuations in HSI. For example, exposure to paper mill effluent (Oikari and Niitylä, 1985), benzo(a)pyrene (Grady et al, 1992) or chromium picolinate (Mehrim, 2012) have not shown any effect on fish HSI. Similarly, our results for GSI, as well as microscopic investigations of chub gonads indicated good reproductive health.…”
Section: Discussionmentioning
confidence: 94%
“…This is in accordance with previous studies, which reported that presence of toxicants in the environment was not always associated with fluctuations in HSI. For example, exposure to paper mill effluent (Oikari and Niitylä, 1985), benzo(a)pyrene (Grady et al, 1992) or chromium picolinate (Mehrim, 2012) have not shown any effect on fish HSI. Similarly, our results for GSI, as well as microscopic investigations of chub gonads indicated good reproductive health.…”
Section: Discussionmentioning
confidence: 94%
“…At 7 mo, findings included numerous clear cell and eosinophilic foci, bile duct proliferation and fibrosis, and a cholangioma. In a second study, brown bullhead were injected with a single intraperitoneal dose of 0, 5, 25, or 125 mg kg -1 benzo[a]pyrene and evaluated over 18 mo (Grady et al 1992); one focus of biliary hyperplasia and fibrosis in a bullhead exposed to 25 mg kg -1 and basophilic foci at all exposure levels were observed at Day 540. None of these lesions were observed in control fish.…”
Section: Discussionmentioning
confidence: 99%
“…The HSI is one of indices most often associated with exposure to contaminants (Grady, Mclaughlin, Caldwell, Schmitt, & Stalling, 1992;Hismayasari, Marhendra, Rahayu, Saidin & Supriyadi, 2015). Likewise, the liver is a primary detoxification organ in fish (Hinton & Laurén, 1990;Liebel et al 2013) and an important target organ related to important metabolic mechanisms.…”
Section: Introductionmentioning
confidence: 99%